2022
DOI: 10.1111/btp.13147
|View full text |Cite
|
Sign up to set email alerts
|

Island size predicts mammal diversity in insular environments, except for land‐bridge islands

Abstract: Insular environments are among the most endangered ecosystems as they face a myriad of anthropogenic stressors. Forest mammals perform a wide range of ecological services, with their persistence being vital for ecosystem functionality in both natural and artificial islands. Studies revealed that shrinkage in island size usually leads to the decay of mammal species richness and abundance in patchy landscapes.However, mammal species-area (SARs) and abundance-area (AARs) relationships can differ among insular env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
2
2
0
Order By: Relevance
“…Other species were not registered in this study in terra‐firme forests but were registered in neighbouring fluvial islands, such as capybaras ( Hydrochoerus hydrochaeris ) and Brazilian porcupine ( Coendou prehensilis ) (Ferreira Neto et al., 2021 ). Indeed, according to the current study, terra‐firme forests harbour more than twice as many species from similar sampling efforts as fluvial islands (Ferreira Neto et al., 2021 ; Neto et al., 2022 ).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Other species were not registered in this study in terra‐firme forests but were registered in neighbouring fluvial islands, such as capybaras ( Hydrochoerus hydrochaeris ) and Brazilian porcupine ( Coendou prehensilis ) (Ferreira Neto et al., 2021 ). Indeed, according to the current study, terra‐firme forests harbour more than twice as many species from similar sampling efforts as fluvial islands (Ferreira Neto et al., 2021 ; Neto et al., 2022 ).…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, according to the current study, terra-firme forests harbour more than twice as many species from similar sampling efforts as fluvial islands (Ferreira Neto et al, 2021;Neto et al, 2022).…”
Section: Mean Detection Probabilitysupporting
confidence: 52%
See 1 more Smart Citation
“…Our study found that island area had a positive relationship with the body dry mass and lipid mass of D. aspericolle , but had a negative relationship with the body dry mass and body size of C. triangularis . Studies have shown that larger islands dwell higher mammal species richness and abundance (Neto et al., 2022; Palmeirim et al., 2018), which are the main providers of food resources for dung beetles (Nichols et al., 2008). Our results partially support the idea that larger islands offer more resources and more stable habitats, since D. aspericolle (but not C. triangularis ) presented proxies of such trend.…”
Section: Discussionmentioning
confidence: 99%